2022
DOI: 10.1186/s12864-022-08656-9
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the rice planthopper egg parasitoid wasps Anagrus nilaparvatae casts light on the chemo- and mechanosensation in parasitism

Abstract: Background Mymaridae is an ancient insect group and is a basal lineage of the superfamily Chalcidoidea. Species of Mymaridae have great potential for biological control. Anagrus nilaparvatae, a representative species of Mymaridae, is ideal for controlling rice planthopper due to its high rate of parasitism and ability to find hosts efficiently in paddy ridges and fields. Results Using both PacBio single-molecule real-time and Illumina sequencing, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
0
5
1
Order By: Relevance
“…A previous phylogeny study based on transcriptomes found that Mymaridae and Trichogrammatidae, two small egg parasitoids, were placed as sister groups of all remaining Chalcidoidea, indicating that small body size and egg parasitoidism were possible ancestral traits of this super family [ 79 ]. Compared with the previous estimation by Ma et al [ 80 ], the range of the estimated age of the divergence between T. pretiosum and three other Trichogramma species increased from 6.4 Mya to 16.9 Mya.…”
Section: Discussioncontrasting
confidence: 76%
“…A previous phylogeny study based on transcriptomes found that Mymaridae and Trichogrammatidae, two small egg parasitoids, were placed as sister groups of all remaining Chalcidoidea, indicating that small body size and egg parasitoidism were possible ancestral traits of this super family [ 79 ]. Compared with the previous estimation by Ma et al [ 80 ], the range of the estimated age of the divergence between T. pretiosum and three other Trichogramma species increased from 6.4 Mya to 16.9 Mya.…”
Section: Discussioncontrasting
confidence: 76%
“…A total of 155 ORs were identified in B. dioryctriae, which is close to the number of ORs in M. mediator (169) [58] and A. mellifera (170) [59] but less than that in N. vitripennis (301) [60]. The different numbers of OR genes in wasps may be affected by species specificity and sequencing technology and depth [20,27]. In Hymenopteran species, a large expansion event of the OR gene family has been found, and gene gain and loss events are common in bees, wasps, and ants [61].…”
Section: Discussionmentioning
confidence: 57%
“…CSPs are soluble carrier proteins that function in a manner similar to OBPs in chemical signal reception in insects [50]. A total of nine CSPs were identified in B. dioryctriae, which is close to the number of CSPs in C. cunea (11) [51], A. nilaparvatae (11) [20] and Aphidius gifuensis (12) [52], but less than that in D. longicaudata (19) [23]. Previous studies have shown that some insect CSPs are expressed exclusively in non-sensory organs (legs, heads, thoraxes, midguts, ovaries, fat body and even the female pheromone glands, etc.)…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations